Does disclosure of enforcement strategies affect tax minimisation? a multi-method approach - Chong, K-Rine; Yusri, Yusniyati; Ong, Tze San; Selamat, Aslam Izah (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Tax gap and tax legitimacy are major concerns in every tax jurisdiction. There are inconsistent findings on the impact of legality and probability of detection on non-compliance behaviour. This study combines economic and socio-psychological elements by exploring how do disclosures of enforcement strategies and legality affect tax minimisation under different tax climate. Multi-method approach is applied with a classroom experiment and a survey which comprises three subgroups, namely postgraduate, employed, and self-employed group. It is discovered that, the experimental subjects assigned under the antagonistic climate will carry on with their tax minimisation decision regardless of the disclosures of enforcements and legality. Interestingly, while such disclosure of enforcements is significant to ‘postgraduate’ and ‘employed’ survey respondents under both climates, legality is only significant to both subgroups under synergistic climate. Without any significant relationships between disclosures and minimisation, self-employed individuals are unresponsive towards enforcements probably because it is easier for them to manipulate their reported income. In sum, perhaps other socio-psychological factors should be prioritised in addition to stringent enforcement to reduce illegal tax minimisation.